A new alligatoroid (Eusuchia, Crocodylia) from the Eocene of China and its implications for the relationships of Orientalosuchina. (November 2021) - Shan, Hsi-yin; Wu, Xiao-Chun; Sato, Tamaki; Cheng, Yen-nien; Rufolo, Scott
Abstract: A new crocodylian, Dongnanosuchus hsui n. gen. n. sp., is described mainly based on four well-preserved skulls from the Eocene Youganwo Formation of the Maoming Basin, southeastern China. It is an alligatoroid and phylogenetically nested within the Orientalosuchina. Dongnanosuchus hsui n. gen. n. sp. differs from all other orientalosuchines primarily in certain features of the skull: (1) a preorbital ridge connects posteriorly with the dorsal orbital rim and a ridge around the anteroventral margin of the orbit, (2) the palatine is short and does not reach the posterior border of the suborbital fenestra, (3) the external mandibular fenestra is closed, and (4) the splenial joins the formation of the mandibular symphysis. The discovery of Dongnanosuchus hsui n. gen. n. sp. confirms the monophyly and North American origin of the Orientalosuchina but suggests that the clade dispersed to Asia via Beringia after diverging from the mainline rather than a sub-lineage of the Alligatoroidea in the Late Cretaceous. UUID: http://zoobank.org/f8ca22f1-6323-462e-bf32-03c6a164c82e .